Giant well-differentiated retroperitoneal liposarcoma, report of a case - Guarniz Poma, Gonzalo Alberto (2023)
Liposarcomas are rare malignant neoplasms that originate in adipose tissue, most frequently in the retroperitoneum. Of all histological variants, differentiated liposarcoma is the most common and has the best prognosis. Diagnosis is established by imaging tests with or without the aid of biopsy. Treatment consists of complete resection of the tumour, which may or may not be accompanied by adjuvant therapy. We present the case of a 41-year-old patient with abdominal distension and weight loss, who was confirmed to have retroperitoneal liposarcoma by abdominal CT scan and underwent successful complete surgical resection. The patient recovered satisfactorily and remained free of recurrence during follow-up. It is concluded that diagnosis and therapy vary according to the characteristics of the tumour and its risk of recurrence, which is why it remains a multidisciplinary challenge to this day.